2019
DOI: 10.1016/j.tjem.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Axillary artery laceration after anterior shoulder dislocation reduction

Abstract: Introduction Glenohumeral dislocation is the most commonly encountered dislocation in the emergency department. The most frequent complications of glenohumeral dislocation are rotator cuff tears and an increase in the risk of recurrent dislocation. Less common acute complications include fractures, neurological complications and vascular injuries. The incidence of axillary artery injury associated with shoulder dislocation is reported to be about 1–2%. Case An 81-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The use of diagnostic modalities such as CT scan with contrast or arteriogram should be performed with a low threshold of suspicion. The literature on axillary artery injury caused by inferior or anterior shoulder dislocation suggests that 1 or more of the following symptoms after reduction should lead to considerations of utilizing further diagnostic modalities: enlarging hematoma in the right axilla, diminished radial and ulnar pulse [ 14 ], sudden increase in pain from the shoulder/axilla [ 8 ], and or hemodynamic instability, as in our patient. The threshold of suspicion should be even lower if the patient has a medical history of recurrent shoulder dislocations, arthro-sclerosis [ 8 ] or age above 60 years old [ 16 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of diagnostic modalities such as CT scan with contrast or arteriogram should be performed with a low threshold of suspicion. The literature on axillary artery injury caused by inferior or anterior shoulder dislocation suggests that 1 or more of the following symptoms after reduction should lead to considerations of utilizing further diagnostic modalities: enlarging hematoma in the right axilla, diminished radial and ulnar pulse [ 14 ], sudden increase in pain from the shoulder/axilla [ 8 ], and or hemodynamic instability, as in our patient. The threshold of suspicion should be even lower if the patient has a medical history of recurrent shoulder dislocations, arthro-sclerosis [ 8 ] or age above 60 years old [ 16 ].…”
Section: Discussionmentioning
confidence: 94%
“…In our case, the debut of axillary artery injury presented when the patient showed signs of hemodynamic instability together with clinical suspicion of an enlarging hematoma in the right axilla 6 hours after reduction. Eyler et al has reported that signs of an enlarging haematoma and diminished radial pulse following anterior shoulder dislocation are characteristic of axillary artery injury [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…History of recurrent dislocations has been reported in up to one-third of the patients 5,18,19 . The type of vascular injury varies between subtle intimal tears and complete vascular lacerations 18,20,21 . The most commonly injured site is the third portion of the axillary artery; however, circumflex, subscapular arteries and axillary vein lacerations have also been described 11 .…”
Section: Discussionmentioning
confidence: 99%
“…High clinical suspicion is essential before and after reduction especially in elderly patients and a history of previous dislocations. Symptoms may include a triad of shoulder dislocation, protruding axillary hematoma, and absent or diminished distal pulses 4,18,21 . However, in some cases as our patient, good peripheral capillary filling, temperature, and palpable pulses may persist even after arterial injury because of the collateral irrigation of the arm; for this reason, pulses do not exclude arterial injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation